Indoor Environmental Factors and Acute Respiratory Illness in a Prospective Cohort of Community-Dwelling Older Adults. (16th April 2020) - Han, Lefei; Ran, Jinjun; Chan, Kwok-Hung; Mak, Yim-Wah; Suen, Lorna; Cowling, Benjamin John; Yang, Lin
Abstract: Background: Ambient environmental factors have been associated with respiratory infections in ecological studies, but few studies have explored the impact of indoor environmental factors in detail. The current study aimed to investigate the impact of indoor environment on the risk of acute respiratory illness (ARI) in a subtropical city. Method: A prospective cohort study was conducted in 285 community-dwelling older adults from December 2016 through May 2019. Individual household indoor environment data and ARI incidence were continuously collected. A time-stratified case-crossover analysis was conducted to estimate the excess risk of ARI associated with per-unit increase of daily mean indoor temperature, relative humidity, and absolute humidity (AH). Result: In total, 168 episodes of ARI were reported with an average risk of 36.8% per year. We observed a negative association of ARI with indoor AH up to 5 lag days in cool seasons, with a 6-day cumulative excess risk estimate of −9.0% (95% confidence interval, −15.9% to −1.5%). Negative associations between household temperature or relative humidity and ARI were less consistent across warm and cool seasons. Conclusions: Lower indoor AH in household was associated with a higher risk of ARI in the community-dwelling older adults in Hong Kong during cold seasons. Abstract : Indoor absolute humidity was negatively associated with acute respiratory illness in cool seasons. The impacts of indoor temperature and relative humidity were less evident.